2021
DOI: 10.1021/acs.analchem.1c01663
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Extraction Technique for Ce Stable Isotopes and Measurement by MC-ICP-MS

Abstract: The separation of Ce from other rare earth elements has not been well established because of their similar geochemical properties. In this study, we report a single-stage extraction technique to purify Ce from natural samples with Eichrom DGA resin. This method separates Ce effectively from matrices and interfering elements, such as Ba, La, and Nd. The Ce elution curve would not drift with different Ce loading masses and rock types. The Ce isotope compositions were measured using a Thermo Scientific Neptune Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In fact, low yield and residual isobaric elements, such as Ce in Nd cuts, have been reported, 45,46 which can severely impact the accuracy and precision of the measurements of stable Ce and Nd isotopes. 12,55 In addition, a long and thin column (0.2 cm × 20 cm) 45 was used in their method, which is time-consuming (∼4 days). 31,46 For the elution scheme (3), Rehkāmper et al 47 reported a two-phase micro-extraction technique for the separation of Ce from the other LREEs, which can be called the NaBrO 3 method 57 or liquid–liquid micro-extraction (LLME).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, low yield and residual isobaric elements, such as Ce in Nd cuts, have been reported, 45,46 which can severely impact the accuracy and precision of the measurements of stable Ce and Nd isotopes. 12,55 In addition, a long and thin column (0.2 cm × 20 cm) 45 was used in their method, which is time-consuming (∼4 days). 31,46 For the elution scheme (3), Rehkāmper et al 47 reported a two-phase micro-extraction technique for the separation of Ce from the other LREEs, which can be called the NaBrO 3 method 57 or liquid–liquid micro-extraction (LLME).…”
Section: Introductionmentioning
confidence: 99%
“…2,9–11,48–50 However, the inconveniences of this method have not been well solved, including (i) the non-reproducibility of the Nd yield (80–100%), which is a noticeable phenomenon for stable Nd isotope analyses; (ii) the residual 10–20% Pr in the Nd cuts, which may cause the molecular interference of 141 PrH on 142 Nd, 40 and data on stable Nd isotopes using the NaBrO 3 method has not been reported so far; (ii) the use of inorganic oxidizing agents (KBrO 3 or NaBrO 3 ) and concentrated HNO 3 , which may cause higher blanks (∼500 pg) 50 and are not easy to operate. For elution scheme (4), some researchers recently reported the use of a TODGA resin column to purify Ce 12 or Nd, 52–54 which has a very high efficiency for LREEs. For example, Bai et al 55 established a single TODGA resin column to separate Nd from the other REEs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations